Impact of a Short-Term Professional Development Teacher Training on Students’ Perceptions and Use of Errors in Mathematics Learning - Kyaruzi, Florence; Strijbos, Jan-Willem; Ufer, Stefan (Frontiers in Education, 2020)
Using errors in mathematics may be a powerful instructional practice. This study explored the impact of a short-term professional development teacher training on (a) students’ perceptions of their mathematics teacher’s support in error situations as part of instruction, (b) students’ perceptions of error situations while learning, and (c) mathematics teacher’s actual error handling practices. Data were gathered from eight secondary schools involving eight teachers and 251 Form 3 (Grade 11) students in the Dar es Salaam region in Tanzania. To explore the effects of a short-term professional development teacher training, we used an exploratory quasi-experimental design with parallel pre-test and post-test instruments. Half of the teachers participated in the short-term professional development training in which they encountered and discussed new ways for utilizing student errors for instruction and provision of (plenary) feedback. Questionnaire scales were used to measure students’ perceptions of errors and perceptions of teacher support in error situations, along with videotaped lessons of plenary feedback discussions. Data were analyzed by latent mean analysis and content analysis. The latent means analysis showed that students’ perceptions of teacher support in error situations (i.e., ‘error friendliness’) significantly improved for teachers who received the training but not for teachers who did not receive it. However, students’ perceptions of anxiety in error situations and using errors for learning (i.e., ‘learning orientation’) were not affected by the training. Finally, case studies of video-recorded plenary feedback discussions indicated that mathematics teachers who received the short-term professional development training appeared more error friendly and utilized errors in teaching.